👤
Steven27
a fost răspuns

Rezolvați următoarele ecuații:
i) 4•(5x - 3) = 3•(x + 7) +1
h) 14•(x + 2) - 5 = 6x +15
j) 16•(2x-1)-4 = 12•(3x-2)​


Răspuns :

Explicație pas cu pas:

i)

[tex]4(5x - 3) = 3(x + 7) +1 \\ 20x - 12 = 3x + 21 + 1 \\ 20x - 3x = 22 + 12 \\ 17x = 34 \\ = > x = 2[/tex]

h)

[tex]14(x + 2) - 5 = 6x +15 \\ 14x + 28 - 5 = 6x + 15 \\ 14x - 6x = 15 - 23 \\ 8x = - 8 \\ = > x = - 1[/tex]

j)

[tex]16(2x-1)-4 = 12(3x-2) \\ 32x - 16 - 4 = 36x - 24 \\ 32x - 36x = - 24 + 20 \\ - 4x = - 4 \\ = > x = 1[/tex]